Anticipazioni wolfiane, filologia e sociologia nelle Quaestiones Romanae di Christian Falster - Santini, Carlo (Classiconorroena, 2016)
The aim of the paper is intended to examine particularly the Quaestiones Romanae of the humanist Christian Falster, who lived and taught lifelong Latin in the Danish kingdom of the early XVIII century. The book is structured formerly according the system of questions and answers, but the exposition begins to become important when the author is giving more attention for the linguistic phenomena of the Latin language and for their evolution in the works of writers, which in my opinion reveals an anticipation of the German philological and historical studies of the forthcoming century. Interesting is also that Falster is gazing on what it means to analyze the patterns of the Roman civilization (the so-called Realien) by a conception which looks like the actually sociology.